The social clause: reality or utopia - Hornung, Sophie Anne (Department of Commercial Law, 2024)
For my final work at the University of Cape Town, I wanted to find a topic which encompassed the issues I studied during my one year in South Africa. The Social Clause turned out to be the perfect issue for my dissertation because it embraced three of the four courses I followed • Human rights, with the human side that underlies the issue; • Labour Law, because productivity is increasingly dictating labour conditions for "thousands and thousands of workers; • Trade Law, in the sense that international trade tends towards the elimination of borders and seeks. to maximise profits, to the detriment of an ethical approach to working conditions. The concept of the Social Clause, which was abstract to me when I began my work, · became familiar to me within weeks. The controversies surrounding the Social Clause, as well as the topicality of this issue at recent summits and other political meetings, showed me that people are not always very aware of what is understood by the term « Social Clause». Therefore, I decided to examine in my dissertation some of the questions and opinions relative to the Social Clause, that arise at the institutional, political and academic levels. I tried to give lectors an overview by summarising the current debates on whether or not to introduce a social aspect in trade, and how to compel states and other economic actors to « play the game » of the Social Clause. In other words, the aim of this dissertation is to tackle the questions and to raise all the other issues ensuing from the Social Clause. My work is far from being complete, exhaustive or innovative on this issue which divides even the economists, lawyers and experts of labour rights. But if I have shed some light on certain realities of the economic world, or simply on the problems of society and its new rules resulting from globalisation, my task will have been fulfilled.